Organizational Development and Change Processes in Educational Institutions, a Challenge for The Management of Education - Garbanzo-Vargas, Guiselle M. (2015)
For the purpose of managing the different processes that educational organizations face in order to reach their organizational development and thus satisfy emergent claims of the context, the present article offers a conceptual review of the principal concepts associated with organizational development. It includes the management of the change processes required as well as the role of the administration of education which must develop intelligent organizations with improved cultures, willing to generate the necessary changes to achieve the organizational vision.  One of its final considerations is that educational management has a key role in the efficient guidance of educational organizations, developing them as intelligent organizations so that they meet high standards in the service they provide which translates into better education for the target population.